Phytochemical Study, in vitro Antioxidant Activities and in vitro Determination of Free Glucose Concentration when Brought into Contact with Extracts of Tetracera rosiflora (Dillenianaceae) Leaves - Christophe Muanyishay Lukanda; Giresse Kasiama Nkal; Williams Balela Balela; Carlos Kabengele Nkongolo; Pierre Luhata Lokadi; Sebastien Luyindula Ndiku; Nadège Ngombe Kabamba; Pius Mpiana Tshimankinda (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Tetracera rosiflora Gilg (Dilleniaceae) is a medicinal plant traditionally used in the Congolese pharmacopoeia to treat various diseases, including diabetes. This study aimed to determine the phytochemical composition, evaluate the in vitro antioxidant potential, and assess the glucose-lowering capacity of T. rosiflora leaf extracts. Phytochemical screening revealed the presence of coumarins, iridoids, anthocyanins, polyphenols, flavonoids, and tannins. Quantitative assays indicated total polyphenols (42.12 ± 1.14 mg GAE/g), flavonoids (0.090 ± 0.002 mg QE/g), and anthocyanins (0.30 ± 0.07 mg CE/g). The quantification of mineral elements by x-ray fluorescence revealed 29 elements with hight conecntration of Ca, K, S and Mg. The organic extracts exhibited strong antioxidant activity by scavenging ABTS and DPPH radicals, with higher efficacy in the ABTS assay (IC50: 5.48 ± 3.23 µg/mL for ethanol extract; 25.65 ± 8.67 µg/mL for dichloromethane extract) compared to DPPH (IC50: 10.81 ± 0.86 µg/mL and 96.16 ± 16.73 µg/mL, respectively). Furthermore, in vitro glucose-binding assays demonstrated that organic extracts markedly reduced free glucose concentrations, confirming their potential antidiabetic activity. These findings support the traditional use of T. rosiflora and highlight its promise as a source of natural antioxidant and hypoglycemic agents.